2019
DOI: 10.2147/cmar.s214405
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Hedgehog signal transducer <em>Smoothened</em> and microRNA-326: pathogenesis and regulation of drug resistance in pediatric B-cell acute lymphoblastic leukemia</p>

Abstract: Purpose Multidrug resistance (MDR) and the subsequent disease relapse are the major causes of childhood acute lymphoblastic leukemia (ALL) related death. The Hedgehog (Hh) signaling pathway can contribute to cancer MDR. In the current study, Smoothened ( Smo ) was selected as the experimental target due to its importance in the Hh pathway in order to evaluate its probable role in pediatric B-ALL drug resistance. Patients and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(52 reference statements)
2
6
0
Order By: Relevance
“…Furthermore, our group has recently identified that overexpression of Smo at the protein level following the downregulation of miR-326 is related to MDR in pediatric B-ALL. Our results revealed a positive correlation between Smo and ABCA3 transcripts in these children (133).…”
Section: Protein-based Biomarkerssupporting
confidence: 60%
“…Furthermore, our group has recently identified that overexpression of Smo at the protein level following the downregulation of miR-326 is related to MDR in pediatric B-ALL. Our results revealed a positive correlation between Smo and ABCA3 transcripts in these children (133).…”
Section: Protein-based Biomarkerssupporting
confidence: 60%
“…[i] Sample issues: Sixteen publications in this systematic review had considerably small sample sizes (30 or less; 26%) [ 36 , 40 , 41 , 46 , 48 , 49 , 58 , 64 , 68 , 69 , 77 , 78 , 80 , 82 , 84 , 86 ]. Larger sample sizes are required to achieve sufficient statistical power and allow for solid conclusions to be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of prognosis and drug sensitivity, study of matched samples before and after therapy is strongly encouraged. Newly diagnosed children with ALL, as well as relapsed and remitted cases, were detected together in five case–control studies included in the present review [ 32 , 41 , 43 , 46 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…intermediate (Farahani et al, 2015). Further, a recent study showed that miR-326 could target the SMO oncogene and suppress the HH signal pathway in the MDR of B-ALL children (Sheybani et al, 2019).…”
Section: Wnt/β -Catenin Canonical Signaling Pathwaymentioning
confidence: 97%